2016
DOI: 10.1186/s12889-016-3011-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of business size in assessing the uptake of health promoting workplace initiatives in Australia

Abstract: BackgroundWorksite health promotion (WHP) initiatives are increasingly seen as having potential for large-scale health gains. While health insurance premiums are directly linked to workplaces in the USA, other countries with universal health coverage, have less incentive to implement WHP programs. Size of the business is an important consideration with small worksites less likely to implement WHP programs. The aim of this study was to identify key intervention points and to provide policy makers with evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 21 publications
2
57
0
1
Order By: Relevance
“…The workplace has been recognised as an important platform for health promotion, and as many employers are investing in initiatives that foster employee wellbeing as part of development of their human resources (Heinen and Darling 2009), the workplace could be instrumental in reducing employee's risk of developing chronic disease (Quintiliani et al 2010). Companies frequently adopt communication strategies and interventions that encourage individuals to make healthier choices when eating at work (Taylor et al 2016), however, canteen food is often criticized for being nutrient-poor, energy-dense and expensive (Sharma et al 2016;Jaworowska et al 2013;Pridgeon and Whitehead 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The workplace has been recognised as an important platform for health promotion, and as many employers are investing in initiatives that foster employee wellbeing as part of development of their human resources (Heinen and Darling 2009), the workplace could be instrumental in reducing employee's risk of developing chronic disease (Quintiliani et al 2010). Companies frequently adopt communication strategies and interventions that encourage individuals to make healthier choices when eating at work (Taylor et al 2016), however, canteen food is often criticized for being nutrient-poor, energy-dense and expensive (Sharma et al 2016;Jaworowska et al 2013;Pridgeon and Whitehead 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In a further study, it was reported that low participation on the part of 'high risk' SME employees is an additional barrier to engagement in workplace health and wellbeing programs [27]. Taylor et al [28] have also demonstrated that one in five SME owner/managers do not believe health promotion activities belong in the workplace, with a further 50% reporting being unsure or undecided. Subsequently, calls have been made [12] to develop greater understanding regarding the motivations of SME owner/managers to engage with workplace health promotion interventions.…”
Section: Workplace Mental Health and The Sme Contextmentioning
confidence: 99%
“…Previous research has reported that up to one fifth of SME owner/managers do not believe that health promotion activities belong in the workplace and are therefore unlikely to promote or engage in these activities [28]. As such, it is clear that more education regarding the benefits of workplace health promotion is needed within this sector, as changing these notions is a first step to increasing uptake of these types of programs [15].…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…In one study focused on workplaces with 50 employees or fewer, there were no significant differences in the adoption of a written smoking policy between workplaces employing 5-9, 10-19, 20-29, and greater than 30 employees (Uslan et al, 2007). In a more recent study conducted in Australia, smoking cessation policies were less common among very small workplaces (fewer than 20 employees), compared to medium (20-200 employees) and large (over 200 employees) worksites (Taylor et al, 2016).…”
Section: Disparities In the Adoption Of Smoking Policies And Activitiesmentioning
confidence: 88%
“…Workplaces employing at least 750 employees have almost seven times the odds of providing a comprehensive health promotion program, compared to workplaces with 50-99 employees (80.5% vs. 29.6%, respectively) (Linnan et al, 2008). Small and very workplaces are also less likely to have smoke and tobaccofree policies in place (Ablah, Dong, & Konda, 2017;Taylor, Pilkington, Montgomerie, & Feist, 2016).…”
Section: Disparities In the Adoption Of Smoking Policies And Activitiesmentioning
confidence: 99%